Assessment of carbon dioxide capture by precipitating potassium taurate solvent. (August 2019) - Moioli, Stefania; Ho, Minh T.; Wiley, Dianne E.; Pellegrini, Laura A.
Highlights: Potassium taurate aqueous solution used for post-combustion CO2 removal. simulations performed in ASPEN Plus®, properly user customized. detailed analyses of the performance of the system. examination of the influence of the solid-liquid separator. high level comparison with some key competitor solvent systems. Abstract: One of the most mature technologies for removal of carbon dioxide from gaseous streams is chemical absorption. Among these, aqueous solutions of amino acids have been considered because of the advantages associated with their being precipitating solvents. This paper presents detailed analyses of the performance of the potassium taurate absorption system by means of a rigorous simulation in a commercial process software (ASPEN Plus®). The profiles of temperature, heat transfer, compositions, and molar flows of carbon dioxide and water have been examined. The operating line and the equilibrium curve for different lean loadings of the solvent are reported and show that the minimium reboiler duty occurs at a lean loading of 0.27. Examination of the influence of the solid-liquid separator on the reboiler duty shows that a recycle split fraction of 0.2 results in the lowest reboiler duty. Different minimum temperature approaches in the lean-rich cross heat exchanger have also been investigated.